A French fish event at the turn of the 10th century? Environment, economy, and ethnicity in maritime Flanders. (27th May 2019) - Oueslati, Tarek
Abstract: Recent excavations in Northern France shed light on new trends in fishing between the 9th and 11th centuries AD. This paper presents the data from two sites characterized by the fishing of large gadids. These finds are contextualized within the broader synchronic regional context and the diachronic local context from the pre‐Roman period to medieval times. From this analysis, it becomes apparent that the sites from Saint‐Georges‐sur‐l'Aa and the neighbouring site of Craywick present innovative fishing tackle and capture grounds along a new type of architecture of the buildings. The skeletal profiles of fish but also of cattle show that the excavated areas were activity zones where butchering was taking place rather than consumption. Some unusual finds such as chopped and burnt fin whale bones and also the manufacture of an object from a rib of whale underline the innovative character of the site. The period around the 10th century seems to be a turning point in the evolution of the occupation of the southern shore of the Channel and hints towards similar changes taking place in Great Britain within the scope of the so‐called fish event horizon.